Electromechanical performance of geopolymer binder with conductive fillers - Li, Xiangquan (Nanyang Technological University, 2021)
Intrinsic self-sensing concrete (ISSC) is an ongoing research topic where it provides another option for structure health monitoring without the use of embedded, attached or remote sensors in concrete. ISSC provides great mechanical properties and self-sensing capability by showing the change in electrical resistivity. Past studies have proven that adding functional fillers such as fibers alters the interface of the matrix of the concrete and improve the mechanical and sensing properties. In this study, microscale carbon fiber (CF) and nanoscale graphene oxide (GO), reduced graphene oxide (rGO) and carbon nanofiber (CNF) will be added into geopolymer concrete to determine if the functional filler could improve the mechanical and sensing properties of the composite. The resistivity of ISSC is measured using a two-probe method under cyclic compression loading. The effect of micro and nano functional fillers on fractional change in resistivity will be assessed to determine the sensitivity of the composite to stress changes.